A study on the occupational health and safety concerns of the employees of the Quezon City Public Library System - Bautista, Jameila Angeli S.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines, 2011)
This study sought to find out (1) the common illnesses and diseases as well as occupational hazards and risks experienced by the library staff of the different units of the Quezon City Public Library System; (2) the most and least common illnesses and diseases they suffered from and how these have affected their job performance, and (3) the preventive measures employed by the library personnel as well as the management to address this problem of occupational health and safety. It was found that (1) occupational illnesses and diseases are present among the employees of the uezon City Public Library System; (2) the employees mostly experienced headache /dizziness, backache / awkward posture, muscle pain, visual/eyestrain, and stiff neck due to stress at work, lack of exercise, and extended use of computers; and that (3) there is a possible adverse effect of these health problems on the library employees' performance on the job. It was, therefore, recommended that management continue implementation of its cleanliness and orderliness drive, conduct staff trainings and seminars, and repair library equipment. Some positive measures to alleviate the most predominant health concerns were likewise recommended.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Industrial safety -- Philippines -- Quezon City; Public libraries -- Philippines -- Quezon City; Library employees -- Philippines -- Quezon City